Effects of low level lead exposure on associative learning and memory in the rat: Influences of sex and developmental timing of exposure. (30th March 2016) - Anderson, D.W.; Mettil, W.; Schneider, J.S.
Highlights: Developmental lead exposure modifies associative learning and memory. Developmental time and size of lead exposure differentially modify associative memory. Outcomes of developmental lead exposure on associative memory differ by sex. Abstract: Lead (Pb) exposure during development impairs a variety of cognitive, behavioral and neurochemical processes resulting in deficits in learning, memory, attention, impulsivity and executive function. Numerous studies have attempted to model this effect of Pb in rodents, with the majority of studies focusing on hippocampus-associated spatial learning and memory processes. Using a different paradigm, trace fear conditioning, a process requiring coordinated integration of both the medial prefrontal cortex and the hippocampus, we have assessed the effects of Pb exposure on associative learning and memory. The present study examined both female and male long evans rats exposed to three environmentally relevant levels of Pb (150 ppm, 375 ppm and 750 ppm) during different developmental periods: perinatal (PERI; gestation—postnatal day 21), early postnatal (EPN; postnatal days 1–21) and late postnatal (LPN; postnatal days 1–55). Testing began at postnatal day 55 and consisted of a single day of acquisition training, and three post training time points (1, 2 and 10 days) to assess memory consolidation and recall. All animals, regardless of sex, developmental window or level of Pb-exposure, successfully acquired conditioned-unconditioned stimulus association during training. However, there were significant effects of Pb-exposure on consolidation and memory recall at days 1–10 post training. In females, EPN and LPN exposure to 150 ppm Pb (but not PERI exposure) significantly impaired recall. In contrast, only PERI 150 ppm and 750 ppm-exposed males had significant recall deficits. These data suggest a complex interaction between sex, developmental window of exposure and Pb-exposure level on consolidation and recall of associative memories.